2014
DOI: 10.1016/s2213-8587(13)70204-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a lifestyle intervention on weight change in south Asian individuals in the UK at high risk of type 2 diabetes: a family-cluster randomised controlled trial

Abstract: National Prevention Research Initiative, NHS Research and Development; NHS National Services Scotland; NHS Health Scotland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(222 citation statements)
references
References 33 publications
7
215
0
Order By: Relevance
“…To date there has been a dearth of evidence concerning T2DM prevention in the UK, with small-scale projects showing mixed results. (7)(8)(9)(10) This study assesses whether the Let's Prevent T2DM programme is effective at preventing progression to T2DM in people with PDM identified through a systematic screening pathway within primary care. Let's Prevent is a pragmatic, relatively low resource, group-based structured-education programme targeting lifestyle behaviour change specifically designed for implementation within a community setting.…”
Section: Usa Diabetes Prevention Program (Dpp)(6)mentioning
confidence: 99%
“…To date there has been a dearth of evidence concerning T2DM prevention in the UK, with small-scale projects showing mixed results. (7)(8)(9)(10) This study assesses whether the Let's Prevent T2DM programme is effective at preventing progression to T2DM in people with PDM identified through a systematic screening pathway within primary care. Let's Prevent is a pragmatic, relatively low resource, group-based structured-education programme targeting lifestyle behaviour change specifically designed for implementation within a community setting.…”
Section: Usa Diabetes Prevention Program (Dpp)(6)mentioning
confidence: 99%
“…Eight randomized controlled clinical trials studies evaluated diet and physical activity interventions in Asian adults [2,5,6,[55][56][57][58][59]. The main characteristics of the included studies are reported in Table 1.…”
Section: Lifestyle Interventions and Prevention Of Type 2 Diabetes Inmentioning
confidence: 99%
“…All T2DM prevention trials performed in Asian populations have been based on a high-risk status defined by blood tests. In all studies, the inclusion criteria indeed required IGT, assessed with oral glucose tolerance test (OGTT), or IFG [2,5,6,[55][56][57][58][59]. All eight RCTs were suitable for inclusion in the meta-analysis showing a a 45 % reduction in the incidence of new T2DM in Asian subjects assigned to the intervention arm (OR 0.55; 95 % CI 0.44-0.70) (Fig.…”
Section: Lifestyle Interventions and Prevention Of Type 2 Diabetes Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, low level of recruitment, retention and follow up of 'high risk' participants has hampered efforts to screen individuals from SA groups [10,11]. In addition to this, lifestyle interventions are often not sufficiently culturally tailored or are not informed by theoretical models and as a result, the methodological quality of relevant studies is often low [12].…”
Section: Introductionmentioning
confidence: 99%